Bridging the gap: social work practice with Indigenous peoples in northern British Columbia - Chaudhary, Sarah (Author); Burke, Susan (Thesis advisor); Dobson, Christina (Committee member); Pearson, Tammy (Committee member); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2020)
This report provides an overview of my practicum placement with a non-profit organization, Carrier Sekani Family Services (CSFS), in particular its Health and Wellness Program. Most of my placement was at Ormand Lake Cultural Healing Camp, known in Carrier language and within the Carrier nations as Choostl’o Bunk’ut. CSFS serves 11 Carrier First Nations bands in north central British Columbia. The objective of my practicum was to gain competency working with Indigenous peoples and their communities and to understand Indigenous wellness from the perspective of the Carrier people. Overall, this practicum helped me to explore my interest in Indigenous mental health and traditional healing. This report will discuss my experiences as a practicum student and will explore how culture can be used for healing in mental health. Several topics that emerged in relation to my practicum goals will be outlined, including ethics and boundaries, spirituality, clinical and alternative practice skills, and integrating Indigenous and Western approaches.